The Effectiveness of the Annual Health Check Model of Using The RCA2 Methodology at the MoPH Clinic, Rajavithi Hospital - Klinthuesin, Sukanda (Journal of The Department of Medical Services, 2025)
Background: In the past, there were issues regarding service recipients encountering delayed access to their health examination results, exceeding 15 business days, and misidentification of recipients in the year 2021, which led to missed opportunities for appropriate treatment in time. However, the researcher used RCA2 (Root Cause Analysis & Actions) methodology to address the issues. This involved conducting a root cause analysis (RCA) and developing a new service model for the 2023 health examination, using IT systems and Lean (Actions) to prevent the recurrence of these issues. Objective: To evaluate the effectiveness of using the RCA2 methodology for analyzing the root cause and developing the new service model. Method: This retrospective descriptive study used a sample of 400 service recipients between January and March 2024. Result: The service recipients identified through RCA2 with abnormal test results were able to access their health examination results via the IT system within 5 business working days at rate of 89.25% (95%CI: 86.21, 92.29). When stratified by target group, the service recipients from Institute of Dentistry had the highest access rate (98.53%), followed by those from central offices of Department of Medical Services (94.63%), and Department of Health Service Support (81.42%). Furthermore, in providing the service based on RCA2, the two points of identification were implemented to prevent misidentification of service recipients: the Kiosk for issuing guidance forms and medical history talking in examination room using the RHIS (Rajavithi Hospital Information System). Moreover, RCA2 helped reduce the number of service steps from 12 to 9 and decreased overall working hours by 1,862 hours (54.41%). Conclusion: The RCA2 methodology has effectively helped analyze the issues and developed the health examination service model.